Perfil de risco das seguradoras de capital aberto listadas na B3 - Pinheiro, Ronery Ekiton Crispino (2022)
The insurance business model aims to minimize the costs associated with pooling the insured's risks. In 2020, the share of the five largest economic groups represented 43% of the total volume of premiums underwritten across the Brazilian market. It is noteworthy that the insurance market, represented by the Superintendence of Private Insurance (SUSEP), adopts a model for capital assessment of the risks inherent to the business. Thus, information disclosure is a critical factor for the efficient functioning of insurance companies, considering that empirical evidence from the stock market indicates that companies with better disclosure display lower cost of equity. Given this context, the present descriptive study, predominantly qualitative in nature, proposed to investigate the risk profile of publicly traded Brazilian insurers listed on B3 from the financial, qualitative and regulatory perspectives altogether. To this end, the period of analysis comprises the period from 2015 to 2020 and the study brings together the seven insurers listed on B3 on 07/31/2021. The data on the financial indicators came from the Economatica database and from the Financial Statements available in the SUSEP Statistical System (SES), which were also used to measure regulatory risk. Furthermore, a content analysis of Section 4 of the Reference Forms was carried out to analyze the risk reporting of insurers under the disclosure approach and a correlation analysis adopted to verify the relationship between the different perspectives of the risk profile of insurers. Results of the financial risk profile pointed to a high-risk index for insurers, especially in 2020. As for the qualitative risk perspective, the content analysis of the reports indicated that the most evident risk factors are those referring to non-financial risks damage subcategory, followed by financial risk factors. From the regulatory perspective, there was a reduction in the need to measure capital in the period under analysis due to the premiums earned and the claims incurred. Finally, in general terms, in the period studied, the correlation analysis showed that there is a strong relationship between risk disclosure and indicators from the financial and regulatory perspectives of risk in the insurers listed on B3